Grammar Rules Matter: Should We Teach Inductively or Deductively? - Bastola, Ganesh (Journal of NELTA, 2016)
The main purpose of this paper is to analyze of Nepalese English language teachers perception of teaching grammar rules. This paper explores whether English teachers teach grammar inductively, deductively or using any other methods. It explores the arguments of teaching grammar rules based on teachers’ perception and my experiences of teaching grammar. Teachers’ perceptions were collected through a mini survey questionnaire. The study found that most of the respondents are in favor of deductive approach/method. A substantial majority of the respondents rated the relevance of GT method because it made learners learn theoretical and pedagogical components in easier manner. Most importantly, the majority valued its relevance abruptly considering a wide repertoire of methods, techniques, activities and resources. A small number of respondents perceived it to be somehow irrelevant and rated it low. In addition, this study reveals that teachers believe in deductive approach as the best way to teach grammar. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page: 31-39